Rayleigh wave azimuthally anisotropic phase velocity maps beneath western Canada. Issue 3 (12th March 2016) - Bao, Xuewei; Eaton, David W.; Gu, Yu Jeffrey
Abstract: The lithospheric evolution of western Laurentia spans several billion years of Earth history and provides an exceptional opportunity for investigating continental deformation during Archean and Proterozoic assembly of the craton and subsequent Phanerozoic orogenic processes along its western margin. In this study we present fundamental‐mode Rayleigh wave azimuthal anisotropy in the period range 20–150 s for western Laurentia and the southern Canadian Cordillera. The surface wave phase velocity maps offer new constraints on the depth distribution of seismic anisotropy in this region. At short periods (20–25 s), strong anisotropy with an orogen‐parallel fast direction is evident in the Cordillera and neighboring foreland belt, suggesting pervasive ductile deformation in the lower crust during Laramide orogenesis. At periods of 70 s and higher, a zone of low‐to‐null azimuthal anisotropy is evident in the southern part of the Cordillera. This apparent null region is interpreted to reflect complex asthenospheric flow due to the combined effects of the Juan de Fuca slab window, lithospheric delamination, and small‐scale edge‐driven convection. Depth‐variant azimuthal anisotropy is evident beneath the cratonic part of the study region. The dominant direction of fast wave propagation in the southeastern part of the craton changes from N‐S at periods of <120 s to NE‐SW at 150 s period. This depth dependence is inferred to arise from different origins of the observed anisotropy, with "frozen" anisotropy within cratonic lithosphere underlain by flow‐driven anisotropy in the asthenosphere. The frozen N‐S trending fabrics in the middle to lower cratonic lithosphere most likely reflect processes of Paleoproterozoic assembly of western Laurentia. Key Points: Orogen‐parallel anisotropy in the Cordilleran lower crust suggests pervasive deformation Weak azimuthal anisotropy in the Cordilleran asthenosphere due to vertical mantle flow Frozen lithospheric fabrics and flow‐driven asthenospheric anisotropy beneath the craton